An 11-year Institutional Review of Nipple-Areolar Complex Tattooing for Breast Reconstruction: Identifying Risk Factors for Development of Tattoo-related Infectious Complications. Issue 5 (November 2021) - Weissler, Jason M.; Kuruoglu, Doga; Curiel, Daniel; Alsayed, Ahmed; Dudakovic, Amela; Harless, Christin A.; Nguyen, Minh-Doan T.
Abstract : Background: Nipple-areolar complex (NAC) tattooing remains a simple and safe procedure, which complements breast reconstruction. This study reviews 11 years of NAC tattooing to identify risk factors for tattoo-related complications. Methods: Patients undergoing NAC tattooing from January 2009 to March 2020 were reviewed. Patient information, reconstructive, and tattoo procedural details were analyzed. Tattoo-related breast infections, defined as breast redness requiring antibiotic therapy within 30 days after tattoo, were captured. Patients with reactive breast redness during the first 2 postprocedural days were excluded. Results: Overall, 539 patients (949 breasts) were included. Implant-based reconstruction (IBR) was performed in 73.6% of breasts (n = 698), whereas 26.4% (n = 251) underwent autologous-based reconstruction (ABR). Acellular-dermal matrix was used in 547 breasts (57.6%). There as a 13.7% (n = 130) of breasts that underwent pretattoo radiation. There was a 65.3% (n = 456) of breasts that underwent subpectoral IBR, whereas 34.7% (n = 242) breasts underwent prepectoral IBR. Tattoo-related infection rate was 2.2% (n = 21 breasts). Mean time to infection was 6.5 ± 5.3 days. There was a 85.7% (n = 18) of infections that occurred in IBR patients, one third occurring in radiated patients. There was a 95.2% (n = 20) of infections that were treated with oral antibiotics only. One explantation was performed after failed intravenous antibiotics. On multivariable analysis, radiation history (odds ratio, 4.1, P = 0.007) and prepectoral IBR (odds ratio, 2.8, P = 0.036) were independent predictors of tattoo-related infection. Among irradiated breasts, breasts with IBR had greater odds of developing tattoo-related infection versus breasts with ABR ( P = 0.025). Conclusions: Although tattoo-related infections were uncommon, previous radiation and prepectoral IBR were both found to be independent predictors of tattoo-related breast infection. There is a role for preprocedural prophylactic antibiotics in these patients to mitigate infectious risk.